1991
DOI: 10.1113/expphysiol.1991.sp003482
|View full text |Cite
|
Sign up to set email alerts
|

The relationships between glucose absorption and insulin secretion and the migrating myoelectric complex in the pig

Abstract: SUMMARYNet glucose and free amino nitrogen absorption and insulin output in the pig hepatic portal vein were calculated from portal-arterial concentration differences and portal blood flow measured by thermodilution. Duodenal and jejunal motility were assessed by electromyography. In the fed pig, the migrating myoelectric complex (MMC) pattern of motility persisted; glucose and amino nitrogen absorption and insulin secretion all varied with the phase of the MMC, rising to maximum values 194+3-1 min before and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 20 publications
4
9
0
Order By: Relevance
“…Additionally, the absorption of a meal is not a smooth process but instead occurs in a rhythmic pattern induced by the migrating myoelectric complex (9,45). This has been observed to entrain insulin secretion (45). Overall, our data from the lixisenatide group agree with those of Lorenz et al (27) obtained in the human in that postprandial insulin secretion appeared to be appropriate to the glucose stimulation.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Additionally, the absorption of a meal is not a smooth process but instead occurs in a rhythmic pattern induced by the migrating myoelectric complex (9,45). This has been observed to entrain insulin secretion (45). Overall, our data from the lixisenatide group agree with those of Lorenz et al (27) obtained in the human in that postprandial insulin secretion appeared to be appropriate to the glucose stimulation.…”
Section: Discussionsupporting
confidence: 76%
“…With 15-to 30-min sampling intervals, the samples may capture concentrations anywhere on the curve from peak to trough. Additionally, the absorption of a meal is not a smooth process but instead occurs in a rhythmic pattern induced by the migrating myoelectric complex (9,45). This has been observed to entrain insulin secretion (45).…”
Section: Discussionmentioning
confidence: 99%
“…In line with these findings, intestinal motility has been shown to correlate positively with intestinal absorption across the intestinal BBM (128,143). Enhanced intestinal motility promotes glucose delivery to BBM transporters by increasing the intestine's functional surface area as well as unsettling the static water layer in the intestine (121,167). Hence, thus far, the evidence supports Cholecystokinin.…”
Section: E889 Regulatory Mediators Of Intestinal Glucose Absorptionsupporting
confidence: 69%
“…Studies in animal models have produced conflicting results, reporting both increases (7,24) and decreases (26,29) in the absorption of glucose during interdigestive phase III activity. This discrepancy may reflect methodological differences, such as in the animal species studied (24,29), the way in which absorption was assessed (7,29), or whether the study was performed under fasting or fed conditions (24,29). A recent study in humans (34) showed a positive association between the rate of glucose absorption and duodenojejunal pressure wave frequency; however, absorption was unaffected by treatment with cisapride.…”
Section: Discussionmentioning
confidence: 97%
“…These results show that an interruption in postprandial small intestinal motility, with migrating bursts of contractions similar to interdigestive phase III activity, reduces the rate of lipid absorption, although glucose absorption is unaffected. Previous studies on the effect of phase III activity on nutrient absorption (7,24,26,29) have been limited to the assessment of glucose absorption in animal models and have yielded conflicting results. In the present study, the concurrent absorption of lipid and glucose was assessed in healthy human subjects, where mucosal dysfunction is not an issue.…”
Section: Discussionmentioning
confidence: 99%